Evaluasi Kebijakan Pendidikan Inklusif di SMA Negeri 1 Penajam Paser Utara - Theodora, Novieta Christina; Komariyah, Laili; Haeruddin; Mulawarman, Widyatmike Gede; Haryaka, Usfandi; Yahya, Masrur (Borneo Educational Journal (Borju), 2025)
Inclusive education is an educational system that ensures equity and equality for all students, including those with special needs, within regular educational institutions. Although the implementation of inclusive education in schools is supported by legal frameworks and national policies, there remain gaps between the policy standards and actual practices in schools, including at SMA Negeri 1 Penajam Paser Utara. This study aims to: (1) describe the implementation of inclusive education policy at SMA Negeri 1 Penajam Paser Utara; (2) identify the barriers to its implementation; and (3) explore solutions to overcome these barriers. This research adopts a qualitative approach using an evaluation method. The findings reveal that: (1) the implementation of inclusive education policy at SMA Negeri 1 Penajam Paser Utara has not fully met the standards set by regulations; (2) the key barriers include the availability of special education teachers, initial assessments, infrastructure, and funding; and (3) proposed solutions involve strengthening resources, improving programs, and requesting additional funding. Inclusive education is expected to be implemented more effectively through systematic and comprehensive improvements at the school level, thereby providing fair and equal services to all students, including those with special needs.